2014
DOI: 10.1111/j.1521-0391.2014.12136.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking among intimate partner violence perpetrators and victims: Findings from the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: Background and Objectives Cigarette smoking and intimate partner violence (IPV) are preventable, major public health issues that result in severe physical and psychological consequences. The primary aim of the current study was to examine the consistency and strength of the association between these highly variable behaviors using a nationally representative sample. Methods Self-reported IPV perpetration, victimization, and smoking data were collected from 25,515 adults (54% female) through the National Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…among both partners (26). In contrast, the Taherkhani et al (27) study did not find a significant relationship between substance and alcohol abuse by one of the partners and domestic violence, while a significant relationship was reported between smoking and violence.…”
Section: Discussionmentioning
confidence: 78%
“…among both partners (26). In contrast, the Taherkhani et al (27) study did not find a significant relationship between substance and alcohol abuse by one of the partners and domestic violence, while a significant relationship was reported between smoking and violence.…”
Section: Discussionmentioning
confidence: 78%
“…As the burden of adversity increases, so does the likelihood of being a current heavy smoker (Anda et al, 1999). Likewise, a well-developed literature on interpersonal partner violence (IPV) during adulthood also shows that victims, as well as their perpetrators, are more likely to smoke than non-victims regardless of relationship type or socioeconomic status (Crane, Hawes, & Weinberger, 2013; Crane, Pilver, & Weinberger, 2014). Trauma exposure also has direct and indirect effects on nicotine dependence and smoking behaviors (Farris et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma exposure also has direct and indirect effects on nicotine dependence and smoking behaviors (Farris et al, 2014). Since the early work linking childhood adversity to smoking, there has continued to be strong support for the adversity, trauma, and smoking relationship from large epidemiological, cross-sectional studies, and, more recently, prospective studies (Bellis, Hughes, Leckenby, Perkins, & Lowey, 2014; Crane et al, 2013; Crane et al, 2014; Edwards, Anda, Gu, Dube, & Felitti, 2007; Elliott et al, 2014; Ford et al, 2011; Taha, Galea, Hien, & Goodwin, 2014; Xie et al, 2012). More specifically, depression and adversity independently predict smoking persistence in patients experiencing serious smoking-related illnesses and increased health risks directly mediated by smoking (Edwards et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, significant associations between IPV perpetration and smoking were not observed; however, previous research suggests a high prevalence of cigarette smoking among men and women in court‐mandated batterer intervention programs. A recent study conducted using NESARC data also demonstrated robust associations between smoking and both IPV victimization and perpetration . This study examined smoking status rather than smoking quantity, and compared levels of IPV perpetration, which are factors that may partially account for differences in results.…”
Section: Discussionmentioning
confidence: 96%